ANALYZING THE CONTENT OF THE PHYSICS BOOKS IN MIDDLE SCHOOL FOR DISTINGUISHED SCHOOLS IN IRAQ IN LIGHT OF SCIENCE STANDARDS FOR THE NEXT GENERATION (NGSS) - Hind Hadi Rayed, Asst Azhar Burhan Ismael (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to find out the availability of next generation science standards (NGSS) in the content of the physics textbooks of the first and second grade of Intermediate School in Schools for the distinguished Students school in Iraq . The sample was consisted of two physics books of the first and second grade of intermediate school .The descriptive analytical method was used in this study. Also, the physics books analysis tool had been prepared in accordance to the next generation physics science standards for the following three essentials : (Disciplinary core ideas, the science and engineering practices and the crosscutting concepts). . The following results had been reached. The three essentials in the physics curriculum books in Middle School of Iraq had applied the standards by (33.33 %), ,The science and engineering practices was the least present standard in the physics curriculum, which was present by only (26%). which was a low percentage and curriculum of grade ten. Also, the disciplinary core ideas in the physics curriculum by a medium level (%39) . the crosscutting concepts (interrelated) was the most present essential (44%),Standards also Varied rates of representation in the two books The research came out with a set of conclusions, recommendations and proposals, the most prominent of which are: The field of scientific and engineering practices is less inclusive, especially engineering design, and it is one of the important pillars on which the science standards for the old generation (NGSS) are based. Conducting comparative studies between curricula to find out the extent to which they achieve science standards for the next generation.